26. Phân tích sự thay đổi mô mềm bằng máy quét khuôn mặt sau phẫu thuật chỉnh hình xương các trường hợp hạng II: Mô tả chùm ca bệnh - Nhật, Nguyễn Đình Minh; Tín, Hồ Sĩ; Chơn, Hồ Nguyễn Thanh; Hải, Đỗ Tiến; Nam, Huỳnh Công Nhật (Tạp chí Nghiên cứu Y học, 2025)
This study aimed to analyze the facial soft tissue characteristics before and after orthognathic surgery in cases of class II malocclusion using 3D facial scanning technology. We performed facial scans of 4 patients before and after surgery at 3 and 6 months. The data, including measurements of particular distances, angles, and ratios, will be analyzed through 3D software measurements as well as qualitative and quantitative assessment of soft tissue changes through the 3D superimposition method. Soft tissue indices were significantly improved after surgery, especially the lip area retreated by 4 - 6mm, the chin area advanced by 2 - 4mm, and the lip-chin angle decreased by 3 - 10 degrees. The ASO surgeries had fewer changes than the BSSO and Lefort I surgeries. According to the VAS, all 4 patients were satisfied with the postoperative facial aesthetic changes. The study showed the degree of visual and objective changes in facial soft tissue after orthognathic surgery, affirming the effectiveness of 3D facial scanning technology in orthognathic surgery, including supporting surgeons in consulting, planning treatment, and evaluating postoperative facial aesthetics.